Pendampingan Keluarga pada Ibu Hamil, Ibu Menyusui, dan Anak Usia di Bawah Dua Tahun (Baduta) di Wilayah Puskesmas Cipadu Kota Tangerang: Family Assistance for Pregnant Women, Breastfeeding Mothers, and Children Under Two Years Old (Baduta) in the Cipadu Community Health Center, Tangerang City - Muntikah Muntikah; Iskari Ngadiarti; Trina Astuti; Syarief Darmawan; Lorenta Marpaung; Sa’diah Multi Karina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Nutrition is one of the factors that play a role in the rate of growth and development of infants as a superior generation in the future. Family mentoring activities are a form of community empowerment by studying existing problems and efforts to overcome them so that families can be free from nutritional problems. This mentoring program aims to help families improve knowledge, feeding practices, and nutritional status before and after family mentoring for pregnant women, breastfeeding mothers, and children under two years old. This activity was carried out using lecture and Focus Group Discussion (FGD) methods, then continued with assistance in feeding practices. Eight respondents comprised three pregnant women, three breastfeeding mothers, and two children under two years old. The implementation began with strengthening cadres regarding child and maternal feeding practices and how to conduct monitoring and evaluation. The mentoring was carried out for two months with weekly monitoring and evaluation. Based on the mentoring results, there was an increase in knowledge among mothers of toddlers, pregnant women, and breastfeeding mothers. In addition, feeding practices also improved, and the weight of children, pregnant women, and breastfeeding mothers also increased. It can be concluded that mentoring focused on feeding practices can improve the nutritional conditions of children and pregnant/breastfeeding mothers who are malnourished.